2012
DOI: 10.1159/000338235
|View full text |Cite
|
Sign up to set email alerts
|

Normative Nasalance Data in Ugandan English-Speaking Children

Abstract: Aims: The aim of this study was to obtain normative nasalance values for typically developing Ugandan English-speaking children as a reference point for clinical practice and further research. Methods: Sixty-nine typically developing Ugandan children (35 males and 34 females, 2.7–13.5 years of age) participated in the study. Nasalance scores were obtained with the Nasometer while children repeated 4 sustained sounds, 14 repeated syllables, 15 sentences (12 oral, 3 nasal) and 2 texts (‘Rainbow Passage’ and ‘Zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
3
14
1
1
Order By: Relevance
“…Additionally, several authors [17,24,35,36,37,38,39] found no significant differences between men and women. Also between boys and girls with a maximum age of 13 years comparable nasalance values have been reported [11,17,18,20,21,22,25,40]. …”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Additionally, several authors [17,24,35,36,37,38,39] found no significant differences between men and women. Also between boys and girls with a maximum age of 13 years comparable nasalance values have been reported [11,17,18,20,21,22,25,40]. …”
Section: Introductionsupporting
confidence: 61%
“…In the literature, a controversy exists about the differences in nasalance values, obtained by the Nasometer [4], for age and gender (table 1). Some authors report low correlations between age and nasalance [10,11,16,17,18,19,20], while others mention significantly lower nasalance values in younger children compared with older children for nasal sentences [21,22] and oral texts [22], or lower nasalance scores for certain speech stimuli in children compared with adults [23,24,25,26]. Possible explanations for these differences are the stronger evidence of coarticulation in adult speakers as a result of speaking experience [27], age-related changes in lymphoid and gland tissue at the velopharyngeal port [28], and the growth of the oropharynx [29] and nasal cavity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Normative nasalance values during repetition of syllables were obtained for speakers of American English (18) and Marathi (19) , Turkish (20) , Egyptian (21) and Ugandan English dialect (22) , as well as for adults speakers of Greek (23) . One of these studies, in particular, determined the nasalance values for Egyptian language speakers, and checked the effect of gender and age in these values (21) .…”
Section: Introductionmentioning
confidence: 99%
“…No significant effects of age or gender on nasality values were obtained in previous studies [19,21]; hence, overall normative values for the groups were reported. The mean DV on the mirror positioned under the patient's nose while articulating nasal sentences increases in the period immediately after tonsillectomy, reflecting the greater opening of the velopharyngeal passageway between the oral vocal tract and the nasal tract, increased airflow through the passageway and subsequent hypernasality.…”
Section: Discussionmentioning
confidence: 77%